Sensory-motor deficits in children with developmental coordination disorder, attention deficit hyperactivity disorder and autistic disorder - Piek, Jan; Dyck, Murray (Elsevier, 2004)
Children who have been diagnosed with any one developmental disorder are very likely to meet diagnostic criteria for some other developmental disorder. Although comorbidity has long been acknowledged in childhood disorders, little is understood about the mechanisms that are responsible for the high level of comorbidity. In a series of studies, we have investigated the link between sensory-motor deficits and developmental disorders. Poor sensory-motor integration has long been implicated as a cause of motor problems in developmental disorders such as developmental coordination disorder (DCD), and our recent research has also investigated sensory-motor deficits in children with attention deficit hyperactivity disorder (ADHD) and autistic disorder. Based on a critical examination of relevant literature and some of our recent research findings, we argue that the importance of poor sensory-motor functioning in discriminating children with different disorders has been underestimated. Poor sensory-motor coordination appears to be linked to DCD, but not ADHD. Also, sensory-motor deficits in children with DCD and autistic disorder may provide insight into some of the social difficulties found in these groups of children. This research will increase our understanding of why children with one developmental disorder typically also have problems in other areas.